THE ROLE OF MILITARY TERMS IN GENERAL MILITARY REGULATIONS - Rashidov Otabek Ziyodullaevich (American Journals, 2023)
Military terminology refers to the terms and language of military organizations and personnel as belonging to a discrete category. As distinguishable by their usage in military doctrine, they serve to depoliticise, dehumanise, or otherwise abstract discussion about its operations from an actual description thereof
Keywords: Operations, the same country, additional complexity, actual description.